2019
DOI: 10.1021/acsami.9b02086
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic Properties of Printed Photogating Carbon Nanotube Thin Film Transistors and Their Application for Light-Stimulated Neuromorphic Devices

Abstract: Artificial synapses/neurons based on electronic/ionic hybrid devices have attracted wide attention for brain-inspired neuromorphic systems since it is possible to overcome the von Neumann bottleneck of the neuromorphic computing paradigm. Here, we report a novel photoneuromorphic device based on printed photogating single-walled carbon nanotube (SWCNT) thin film transistors (TFTs) using lightly n-doped Si as the gate electrode. The drain currents of the printed SWCNT TFTs can gradually increase to over 3000 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 50 publications
0
97
0
1
Order By: Relevance
“…Particularly, photonic synapse devices have received attention because they have several advantages compared to the electronic synapse devices, such as wide bandwidth, low crosstalk, and low power consumption characteristics 18–28. Therefore, researchers have attempted to mimic synaptic behaviors by utilizing optical stimulation and photonic synapse devices have been realized with various materials such as carbon nanotubes,29,30 oxide semiconductors,18,19,25,31,32 perovskite quantum dots,21,33 2D materials,23,24,27,28,34,35 and hybrid perovskites 20,26,36. These devices have demonstrated synaptic functions, such as short‐term plasticity (STP), paired‐pulse facilitation (PPF), long‐term plasticity (LTP), STP‐to‐LTP transition, and spike‐timing‐dependent plasticity by optical stimulation.…”
Section: Figurementioning
confidence: 99%
“…Particularly, photonic synapse devices have received attention because they have several advantages compared to the electronic synapse devices, such as wide bandwidth, low crosstalk, and low power consumption characteristics 18–28. Therefore, researchers have attempted to mimic synaptic behaviors by utilizing optical stimulation and photonic synapse devices have been realized with various materials such as carbon nanotubes,29,30 oxide semiconductors,18,19,25,31,32 perovskite quantum dots,21,33 2D materials,23,24,27,28,34,35 and hybrid perovskites 20,26,36. These devices have demonstrated synaptic functions, such as short‐term plasticity (STP), paired‐pulse facilitation (PPF), long‐term plasticity (LTP), STP‐to‐LTP transition, and spike‐timing‐dependent plasticity by optical stimulation.…”
Section: Figurementioning
confidence: 99%
“…In addition to combining with semiconductors, carbon nanotubes assisted in lightly n‐doped Si transistor can also realize the emulation of synaptic behaviors. Shao et al showed a simple synaptic transistor based on single‐walled carbon nanotubes (SWCNTs) using HfO 2 as the gate dielectric and lightly n‐doped Si as the gate electrode (Figure a) . An interesting phenomenon can be observed as shown in Figure b that once the light is turned on, the current of the device decreases rapidly, whereas the current increases and maintains stable when the light is removed.…”
Section: Emerging Materials‐based Synaptic Devicesmentioning
confidence: 99%
“…The inset in panel (d) represents the schematic of lowpass filtering of a synapse. Reproduced with permission . Copyright 2019, American Chemical Society.…”
Section: Emerging Materials‐based Synaptic Devicesmentioning
confidence: 99%
“…CNTs as another nanomaterial have been utilized in fabricating conductive inks because of their extraordinary electrical, optical, and mechanical properties. [81][82][83] He and Tjong 8 prepared a kind of conductive ink containing 0.1 wt% multi-walled CNTs (MWNTs) and 0.2 wt% GO. The conductive ink was utilized in the scalable production of conductive lms with a sheet resistance of 380 U sq À1 and 85% transparency.…”
Section: Carbon Nss and Npsmentioning
confidence: 99%